THE COASTAL CURRENT SOUTH OF JAVA - Soeriaatmadja, Raden E. (Marine Research in Indonesia, 1957)
This paper concerns investigations of the hydrography of the waters south of Java, especially of the Java Coastal Current, which have been carried out by the Institute of Marine Research at Djakarta. It is based on (1) oceanographic observations made by the research vessel "SAMUDERA" in February 1957, (2) the surface salinity data of the years 1949?1955, consisting of about 700 observations which were collected by the Institute of Marine Research at Djakarta, and (3) the surface current data obtained from the Atlas of Oceanographic and Meteorological data of the Koninklijk Nederlands Meteorologisch Instituut.